Budaya dan Kualitas Hidup Lansia di Pelayanan Sosial Lanjut Usia: Systematic Review - Raharjo, Shafana Azzahra; Larasati, TA; Kusumaningtyas, Intan; Utama, Winda Trijayanthi (CV. Jasa Sukses Abadi, 2024)
Aging is a natural process experienced by all living beings, marked by physiological, psychological, and social changes in individuals over the age of 60, as well as a decline in functional capacity and structural changes in the body. Many elderly individuals reside in social care facilities, which, although providing care for the neglected or less fortunate elderly, often face negative views from society, especially those that adhere to strong family values, which can affect their quality of life. This study examines the culture and quality of life of elderly individuals living in social care facilities through a systematic review. Data were gathered from relevant articles using related keywords from various databases. The findings of this study indicate that elderly individuals residing in social care facilities tend to have lower quality of life, due to limited social interactions and health-related issues. Factors influencing the quality of life of the elderly include physical, social, psychological, and environmental aspects, which are often affected by health conditions, physical limitations, and the lack of social interactions in social care facilities. On the other hand, cultural values also play a role in shaping societal views of social care facilities, particularly in regions with strong family-oriented values. Recommendations to improve the quality of life for the elderly include increasing attention to both their physical and psychological health, while ensuring that cultural values are respected in elderly social care services.